Secretory function in subplate neurons during cortical development - Kondo, Shinichi; Al-Hasani, Hannah; Hoerder-Suabedissen, Anna; Wang, Wei Zhi; Molnár, Zoltán (Frontiers in Neuroscience, 2015)
Subplate cells are among the first generated neurons in the mammalian cerebral cortex and have been implicated in the establishment of cortical wiring. In rodents some subplate neurons persist into adulthood. Here we would like to highlight several converging findings which suggest a novel secretory function of subplate neurons during cortical development. Throughout the postnatal period in rodents, subplate neurons have highly developed rough endoplasmic reticulum (ER) and are under an ER stress condition. By comparing gene expression between subplate and layer 6, we found that several genes encoding secreted proteins are highly expressed in subplate neurons. One of these secreted proteins, neuroserpin, encoded by the serpini1 gene, is localised to the ER in subplate cells. We propose that subplate might influence cortical circuit formation through a transient secretory function.